The energetics of muscle contractions resembling in vivo performance - Curtin, N. A.; Barclay, C. J. (Journal of Biomechanics, 2023)
Muscle energetics has expanded into the study of contractions that resemble in vivo muscle activity. A summary is provided of experiments of this type and what they have added to our understanding of muscle function and effects of compliant tendons, as well as the new questions raised about the efficiency of energy transduction in muscle.